(ii) Prove by induction that, for all positive integers n, f(n) = 3^(3n–2) + 2^(3n+1) is divisible by 19

Let P(n) represent the statement that 'f(n) is divisible by 19'. For the basis step, I prove that P(1) is true: f(1) = 33(1)-2+ 23(1)+1 = 19. 19 is divisible by 19 so P(1) is true. I now want to prove that P(k) implies P(k+1) for all positive integers k. I therefore assume P(k), and I can write: 33k-2+ 23k+4 = 19m for some positive integer m. f(k+1) = 33k+1+23k+4 = 27(33k-2) + 8(33k+1) = 8(33k-2+23k+1) + 19(33k-2). I now substitute my assumption: f(k+1) = 19(8m + 33k-2). So P(k) implies P(k+1). Since P(1) is true, P(n) is therefore true for all positive integers n as required.

Answered by Daniel L. Maths tutor

8533 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Integrate | x^7 (ln x)^2 dx ( | used in place of sigma throughout question)


Using the product rule, differentiate: y = (x^2 - 1)(x^3 + 3).


differentiate: y^2 + 3xy + x + y = 8


integrate (4x^3 +3)(x^4 +3x +16)^2 dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences